A water-based photocurable conductive paint, and a preparation method and application thereof

CN118496753BActive Publication Date: 2026-10-16GUANGDONG RONGZHIBANG NEW MATERIAL TECH CO LTD
View PDF 11 Cites 0 Cited by

Patent Information

Application Number
CN202410553831.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-05-07
Publication Date
2026-10-16
Estimated Expiration
2044-05-07

AI Technical Summary

Technical Problem

[0005]本发明的目的在于克服现有的电子乐器涂料所涉及到的有大量的挥发性溶剂、无法起到保证电路中电流顺畅流通的作用,也无法起到减少外部电磁场对电路影响效果的缺点,提供一种水性光固化导电涂料

Benefits of technology

[0065] 1. The water-based photocurable conductive coating of the present invention uses water to replace part of the solvent, which can reduce the harm to the human body during the production and application process of the coating. The water-based photocurable conductive coating of the present invention can form a uniform conductive film on the surface of the substrate, ensuring the stability of the connection between electronic components and the reliability of signal transmission. The conductive coating can be used to provide local electromagnetic shielding, reducing the impact of external electromagnetic interference on the substrate. The water-based photocurable conductive coating can also provide good mechanical properties and environmental resistance, further extending the service life of the substrate.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004825346090000161
    Figure BDA0004825346090000161
  • Figure BDA0004825346090000171
    Figure BDA0004825346090000171
  • Figure BDA0004825346090000181
    Figure BDA0004825346090000181
Patent Text Reader

Abstract

The application belongs to the technical field of water-based paint, and particularly relates to a water-based photocuring conductive paint, a preparation method and application thereof. The water-based photocuring conductive paint comprises the following components in parts by weight: modified polyurethane acrylate 30-50 parts, conductive material 10-30 parts, coupling agent 1-3 parts, leveling agent 0.5-1.5 parts, photoinitiator 3-6 parts, water 20-35 parts, cosolvent 10-20 parts, and additive 8-15 parts. The water-based photocuring conductive paint uses water to replace part of the solvent, can reduce the harm of the paint to the human body in the production and application process, can form a uniform conductive film on the surface of the substrate, ensures the stable connection between electronic components and the reliability of signal transmission, can be used to provide local electromagnetic shielding, reduces the influence of external electromagnetic interference on the substrate, and can also provide good mechanical properties and environmental resistance, further prolonging the service life of the substrate.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of water-based coating technology, and particularly relates to a water-based photocurable conductive coating, its preparation method and application. Background Technology

[0002] Musical instruments play a vital role in musical performance and composition, not only producing beautiful melodies but also expressing rich emotions and feelings. Different types of instruments possess unique timbres and playing characteristics, making them suitable for various styles and genres of musical works. As people's material living standards improve, their pursuit of spiritual enrichment also increases. Musical instruments, as a vehicle for refined art, are widely used in schools, public squares, and various evening events, with participants ranging from teenagers and young adults to the elderly, including amateur enthusiasts and professional cultural and artistic workers.

[0003] Electronic musical instruments are instruments manufactured using electronic and digital audio technologies. They can simulate the sounds of traditional instruments or create entirely new timbres and effects. There are many types of electronic musical instruments, including electronic keyboard instruments, synthesizers, electronic drums, electronic guitars, and electronic flutes. Electronic musical instruments use specific methods to trigger electronic signals, employing electronic technology to produce sound through electroacoustic devices. They typically have a special electronic sound-producing body, composed of several electronic components forming a converter. Through voltage amplification, different wavelength changes produce different tones, which are then amplified further and transmitted through a speaker to produce the specific sound. In some electronic musical instruments, wires and metal foils are used in the circuitry to ensure the correct flow of current. If a part of the circuitry has poor conductivity, it can lead to sound distortion, increased noise, or decreased volume. Simultaneously, poor contact of the metal foils can weaken the anti-interference capability, making it difficult to effectively reduce the influence of external electromagnetic fields on the circuitry.

[0004] Currently, solvent-based unsaturated polyester coatings are widely used for coating musical instruments. For example, Chinese patent document CN104293127A discloses a special unsaturated polyester primer for musical instruments, which contains a large amount of toluene, a volatile diluent. Toluene not only harms the health of coating workers but also poses a threat to the health of instrument users. Furthermore, unsaturated polyester cannot ensure smooth current flow in the circuitry of electronic musical instruments, nor can it reduce the influence of external electromagnetic fields on the circuitry. Therefore, there is a need to develop a water-based, UV-cured conductive coating to meet the more stringent coating processes and the higher quality requirements of electronic musical instruments. Summary of the Invention

[0005] The purpose of this invention is to overcome the shortcomings of existing electronic musical instrument coatings, which involve a large amount of volatile solvents, cannot ensure the smooth flow of current in the circuit, and cannot reduce the influence of external electromagnetic fields on the circuit, and to provide a water-based photocurable conductive coating.

[0006] The present invention adopts the following technical solution:

[0007] A water-based photocurable conductive coating comprises the following components in parts by weight: 30-50 parts modified polyurethane acrylate, 10-30 parts conductive material, 1-3 parts coupling agent, 0.5-1.5 parts leveling agent, 3-6 parts photoinitiator, 20-35 parts water, 10-20 parts cosolvent, and 8-15 parts additives.

[0008] Specifically, modified polyurethane acrylate, as the main component of the coating, improves the mechanical properties and chemical stability of the coating, and provides flexibility, abrasion resistance, and adhesion. Conductive materials are responsible for providing the conductivity of the coating, and coupling agents can improve the interfacial bonding between the conductive materials and the polymer matrix, thereby improving conductivity and the mechanical strength of the coating. Leveling agents help the coating form a smooth surface during the drying process, reducing defects such as unevenness, orange peel, and pinholes. Photoinitiators decompose under ultraviolet or visible light irradiation, generating free radicals that initiate polymerization reactions of groups in the coating. Water, as an environmentally friendly solvent, is used to adjust the viscosity and solids content of the coating, making it suitable for coating and effectively reducing the emission of volatile organic compounds. Cosolvents are used to assist in dissolving the components in the coating, ensuring the uniformity and stability of the coating. Additives are used to improve the processing performance, storage stability, and performance of the coating.

[0009] Furthermore, the modified polyurethane acrylate is a bisphenol A epoxy acrylate modified polyurethane acrylate. The modified polyurethane acrylate combines the high strength, good adhesion, and chemical resistance of epoxy resin with the flexibility, abrasion resistance, and photocuring properties of polyurethane, resulting in a modified material that not only has rapid curing capabilities but also superior physical and mechanical properties and environmental resistance, making it suitable for complex surface treatments or multi-material applications. The network structure formed by the modification with bisphenol A epoxy acrylate helps to more uniformly disperse conductive materials, increasing their load-bearing capacity and creating a continuous conductive path, thus enhancing the conductive shielding effect. The low viscosity and rapid curing characteristics of the modified polyurethane acrylate make construction more convenient, allowing for use over a wider temperature range. The cured film has high gloss, stable color, and is less prone to yellowing. The introduction of epoxy acrylate enhances the chemical stability of the coating, improving its resistance to corrosive media such as acids, alkalis, and solvents, and also improves the suitability of the conductive shielding coating for outdoor use.

[0010] Further, the modified polyurethane acrylate is prepared as follows: polyether diol, diisocyanate, dimethylolpropionic acid, and acrylate are added to a closed reactor and reacted to obtain a polyurethane acrylate prepolymer emulsion; bisphenol A epoxy acrylate is dissolved in an appropriate amount of solvent and then gradually added to the above A1 prepolymer emulsion, and under gentle stirring, it is ensured to be uniformly dispersed and form a stable emulsion; triethylamine is added for ring opening and neutralization, deionized water is added, and shear dispersion is performed to obtain the modified polyurethane acrylate emulsion.

[0011] Optionally, in some embodiments, polyether diol is used as the soft segment, comprising 20-50 parts by weight; diisocyanate is used as the hard segment, with a ratio of 1:1 to 1:5 with the polyether diol; dimethylolpropionic acid, as the acidic functional group in the reaction, provides hydroxyl groups to react with the isocyanate groups, and simultaneously competes with the acrylate monomers for reaction with the isocyanate groups to adjust the molecular weight and hydrophilicity, and is used in an amount of 5-20 parts. The acrylate can adjust the hydrophilicity of the polymer, the photocuring rate, and the final coating properties, and is used in an amount of 5-50 parts.

[0012] Specifically, the first step is to prepare a polyurethane acrylate prepolymer emulsion. Under well-ventilated conditions, in a reactor equipped with a stirrer, thermometer, and nitrogen inlet, polyether diol and a certain amount of butyl acetate are added. The mixture is dehydrated for 1-2 hours at a temperature of 105-115℃ and a vacuum of -0.080-0.086 MPa. The temperature is then lowered to 50-55℃, diisocyanate is added, and the temperature is raised to 80-85℃. The catalyst DBTDL is added, and the reaction is continued for 1-2 hours. The temperature is then lowered to 30-40℃, dimethylolpropionic acid is added, and hydroquinone, a polymerization inhibitor, is added to prevent further crosslinking. The reaction is continued for 0.5-2 hours, and the mixture is cooled to room temperature. Hydroxyethyl methacrylate is then added, and the mixture is stirred and reacted for 2 hours under reflux at 60-80℃. Triethylamine is added as a neutralizing agent to adjust the pH value. Under stirring, water is slowly added until a stable emulsion is formed, thus obtaining the polyurethane acrylate prepolymer emulsion.

[0013] The second step is to prepare the bisphenol A epoxy acrylate modified polyurethane prepolymer. The synthesized polyurethane acrylate prepolymer emulsion is stirred until homogeneous, and the temperature is controlled at 70-75℃. Bisphenol A epoxy acrylate dissolved in an appropriate amount of ethanol is added, and the reaction is carried out for 1-2 hours. The temperature is then lowered to 50-55℃, and a ring-opening agent, organotin alcohol or triethylamine, is added. The reaction is stirred for 2-3 hours. The temperature is further lowered to 30-40℃, and triethylamine is added to neutralize the reaction for 30-45 minutes. Under high-speed stirring, 20-50 parts of deionized water are added, and the mixture is sheared and dispersed for 45-60 minutes to obtain the bisphenol A epoxy acrylate modified polyurethane emulsion.

[0014] Furthermore, the conductive material includes modified graphene, polyvinyl alcohol graft copolymer, and modified multi-walled carbon nanotubes.

[0015] Furthermore, the modified graphene is polyvinyl alcohol-modified graphene oxide. Polyvinyl alcohol can effectively disperse graphene oxide in the coating, forming a stable and uniform dispersion system, preventing graphene oxide from agglomerating or precipitating in the coating, and ensuring the stability of conductivity. The hydroxyl groups of polyvinyl alcohol can form hydrogen bonds and other interactions with the oxygen-containing functional groups on graphene oxide, thereby introducing new reaction sites, enhancing the bonding force between graphene oxide and the coating matrix, and helping to form a denser composite material structure, improving the adhesion, wear resistance, and durability of the coating. Polyvinyl alcohol modification can effectively improve the conductivity of graphene oxide, and can, to a certain extent, control the density and continuity of the graphene oxide network, giving the coating better conductivity. Polyvinyl alcohol modification can also improve the antioxidant properties of graphene oxide, making it more stable in the coating, extending the coating's service life and performance.

[0016] The preparation method of polyvinyl alcohol modified graphene oxide involves adding graphene oxide powder to dimethyl sulfoxide and subjecting it to ultrasonic treatment to obtain a uniformly dispersed graphene oxide solution. EDC·HCl (1-ethyl-3-(3-dimethylaminopropyl)carbodiimide hydrochloride) and NHS (N-hydroxysuccinimide) are then added to the graphene oxide solution. These two reagents convert the carboxyl groups of the graphene oxide into more reactive intermediates. Polyvinyl alcohol is then dissolved in water to form a polyvinyl alcohol (PVA) aqueous solution.

[0017] Activated graphene oxide was slowly added to an aqueous solution of polyvinyl alcohol (PVA) while maintaining the temperature at approximately 60°C and stirring for 4 hours. This allowed the hydroxyl groups of PVA to condense with the activated carboxyl groups of graphene oxide, forming amide bonds. During the esterification reaction, the hydroxyl groups of PVA condensed with the carboxyl groups of graphene oxide, forming ester bonds, thus grafting PVA onto the surface of graphene oxide. The product was then separated from the solution by centrifugation or filtration, purified, and dried to obtain polyvinyl alcohol-modified graphene oxide.

[0018] Optionally, in some embodiments, polyvinyl alcohol-modified graphene oxide is added to dimethyl sulfoxide or water and dispersed using ultrasonication to form a stable polyvinyl alcohol-modified graphene oxide dispersion. (For later use.)

[0019] Polyvinyl alcohol (PVA) graft copolymers are polyvinyl alcohol-grafted polyaniline (PAAG) copolymers. The addition of PVA improves the processing properties of the material, making conductive coatings based on PVA-grafted PAAG easier to apply. Conventional coating and spraying methods can be used to form a uniform conductive coating. By grafting hydrophilic PVA, the dispersibility and solubility of the copolymer in aqueous and other polar solvents can be improved. This avoids the difficulty of dissolving polyaniline in common solvents due to its rigid backbone and strong intermolecular interactions. The grafted PVA acts as a steric barrier, reducing the aggregation between polyaniline chains, thus contributing to the formation of a more uniform conductive network and improving the conductivity of the coating. The introduction of PVA may improve the thermal stability and environmental tolerance of the copolymer, as PVA can act as a protective layer, reducing the direct exposure of polyaniline chains. PVA has good film-forming and adhesive properties, which helps improve the adhesion between the coating and the substrate. It is also compatible with various resins and additives, thereby enhancing the overall performance of the coating. The hydroxyl groups of PVA can form hydrogen bonds with polyaniline, promoting electron migration and thus improving conductivity.

[0020] The preparation method of polyvinyl alcohol grafted polyaniline copolymer is as follows: a certain amount of polyvinyl alcohol (PVA) is dissolved in deionized water, heated to boiling, stirred continuously until completely dissolved, and then cooled to room temperature.

[0021] An appropriate amount of aniline monomer dissolved in N-methylpyrrolidone was added to a polyvinyl alcohol (PVA) solution, and a small amount of glacial acetic acid was added to adjust the pH to acidic. Then, an appropriate amount of ammonium persulfate was added as an oxidant. Under stirring conditions, the reaction was maintained between room temperature and 60°C for 2-4 hours until the reaction was complete. The product was then washed and dried to obtain a polyvinyl alcohol-grafted polyaniline copolymer.

[0022] Optionally, in some embodiments, the polyvinyl alcohol (PVA) is of medium to high molecular weight, the PVA solution prepared with deionized water is between 5% and 15%, the mass ratio of aniline monomer to polyvinyl alcohol is 1:1 to 1:5, the mass ratio of aniline monomer to N-methylpyrrolidone is 1:1.1 to 1:2, glacial acetic acid is used to adjust the pH value to 3-5, and the amount of ammonium persulfate is 0.5-2% of the aniline monomer.

[0023] Furthermore, the modified multi-walled carbon nanotubes are carboxylic acid multi-walled carbon nanotubes modified with γ-aminopropyltriethoxysilane. γ-aminopropyltriethoxysilane can introduce hydrophilic amino and ethoxy groups, which helps improve the dispersibility of multi-walled carbon nanotubes in polar solvents, thus facilitating the preparation of uniform conductive coatings. γ-aminopropyltriethoxysilane can effectively improve the surface properties of carbon nanotubes, enhance their compatibility with the coating matrix, and improve the adhesion and stability of the coating. Good dispersibility and interfacial adhesion can reduce the contact resistance between carbon nanotubes. The modified multi-walled carbon nanotubes help lower the percolation threshold of the conductive coating, meaning that good conductivity can be achieved at a lower addition amount. Silane modification can improve the oxidation resistance of carbon nanotubes, extending the service life and stability of the conductive coating. Silane modification can enhance the wear resistance of carbon nanotubes, giving the coating better durability and corrosion resistance.

[0024] The modified multi-walled carbon nanotubes are prepared by adding an appropriate amount of multi-walled carbon nanotubes to glacial acetic acid and dispersing them using ultrasonic treatment to form a multi-walled carbon nanotube suspension, thus preventing the aggregation of multi-walled carbon nanotubes. A mixture of concentrated nitric acid and concentrated sulfuric acid is prepared at a volume ratio of 1:3.

[0025] The dispersed multi-walled carbon nanotube suspension was slowly added to a pre-prepared mixture. The mixture was reacted at room temperature to 60°C for 4 hours with slow stirring to control the reaction rate and reduce the risk of explosion. After the reaction was complete, the mixture was poured into a large amount of ice water to neutralize excess acid, followed by multiple washes with water until the pH was close to neutral. Finally, it was washed with ethanol to remove residual water and impurities, and the washed carboxylic acid multi-walled carbon nanotubes were collected by vacuum filtration.

[0026] Carboxylic acid multi-walled carbon nanotubes were dispersed in ethanol and ultrasonically dispersed to form a homogeneous dispersion. The dispersion of carboxylic acid multi-walled carbon nanotubes was adjusted to weakly alkaline or neutral with sodium hydroxide.

[0027] γ-aminopropyltriethoxysilane was added to a dispersion of carboxylic acid multi-walled carbon nanotubes. The mass ratio of γ-aminopropyltriethoxysilane to carboxylic acid multi-walled carbon nanotubes was between 1:10 and 1:50.

[0028] After adding γ-aminopropyltriethoxysilane, the mixture was stirred at room temperature to 60°C for 2 hours to promote the reaction between γ-aminopropyltriethoxysilane and the carboxyl groups on the surface of carboxylic acid multi-walled carbon nanotubes. The product was washed and dried to obtain γ-aminopropyltriethoxysilane-modified carboxylic acid multi-walled carbon nanotubes.

[0029] Furthermore, the coupling agent is one or both of vinyltrimethoxysilane and γ-methacryloyloxypropyltrimethoxysilane, and the leveling agent is BYK-333 or GSK-550.

[0030] Specifically, vinyltrimethoxysilane and γ-methacryloxypropyltrimethoxysilane contain vinyl and methoxy groups, respectively, and can bind to unsaturated double bonds in the emulsion or through free radical polymerization. Simultaneously, their siloxane groups can chemically interact with the surfaces of inorganic fillers or reinforcing materials, such as conductive materials, forming strong chemical bridges and enhancing the adhesion between the coating and the filler. Through the modification effect of coupling agents, the tendency of conductive materials to agglomerate in the matrix can be effectively reduced, achieving more uniform dispersion. Uniformly dispersed conductive materials help improve the mechanical properties of the coating, such as hardness, toughness, and abrasion resistance, while also improving the coating's corrosion resistance, weather resistance, and thermal stability. Good interfacial bonding reduces the possibility of water or other corrosive media penetration.

[0031] Optionally, in some embodiments, vinyltrimethoxysilane can participate in the crosslinking reaction of the polymer, increasing the three-dimensional network structure of the coating and further improving its physical and mechanical properties and chemical stability.

[0032] BYK-333 is a polyether-modified silicone that significantly reduces the surface tension of coatings, helping to eliminate defects such as orange peel and pinholes in the coating film, resulting in a smoother and more even surface. By promoting the release of air in the coating film, it reduces the generation of surface defects such as pinholes and bubbles, with minimal impact on the transparency and color stability of the coating.

[0033] GSK-550 is a non-silicone leveling agent that effectively promotes the flow of paint on the substrate, helping to form a uniform coating. It helps eliminate problems such as brush marks and sagging caused by poor paint flow. GSK-550 also improves the scratch resistance and hardness of the coating.

[0034] Further, the photoinitiator is one or more of 2-hydroxy-4-(2-hydroxyethoxy)-2-methylphenylacetone, 2-hydroxy-2-methyl-1-phenyl-1-propanone, 1-hydroxycyclohexylphenyl ketone, and ethyl 2,4,6-trimethylbenzoylphosphonate, and the cosolvent is polyvinylpyrrolidone.

[0035] Specifically, 2-hydroxy-4-(2-hydroxyethoxy)-2-methylphenylacetone exhibits good water solubility and low skin irritation, along with a wide absorption range and high photoinitiation efficiency. 2-hydroxy-2-methyl-1-phenyl-1-propanone is a highly efficient free radical photoinitiator, particularly suitable for thick-film photocuring applications due to its good light penetration depth and photoinitiation efficiency. It also possesses better solubility and compatibility, contributing to improved coating transparency and gloss. 1-Hydroxycyclohexylacetone is suitable for deep-curing and high-solids-content coating systems. Its low volatility and low hygroscopicity enhance the weather resistance and chemical resistance of coatings. Ethyl 2,4,6-trimethylbenzoylphosphonate exhibits strong absorption in the visible light region, enabling polymerization under longer wavelengths of light, facilitating curing through thicker coatings, and is suitable for photocuring systems containing pigments or fillers. It remains stable over a wide pH range and exhibits low temperature sensitivity, which is beneficial for storage and application.

[0036] Polyvinylpyrrolidone (PVP) is a non-toxic, hydrophilic, and soluble polymer that is miscible with various high and low molecular weight substances or forms emulsions. It exhibits excellent chemical stability, complexing properties, and surface activity. Due to the presence of polar pyrrolidone groups in its molecule, PPVP can adsorb onto the surface of conductive materials. Through steric hindrance and electrostatic stabilization, it prevents particle aggregation, thus providing good dispersion stability in coating systems and contributing to the formation of a uniform conductive network. Furthermore, PPVP does not remain on the coating surface after drying, contributing to the formation of a continuous and dense coating. By improving the flowability and processing properties of the coating, it makes the coating easier to apply and results in a smoother surface.

[0037] Further, the additives include film-forming aids, defoamers, thickeners, substrate wetting agents, matting agents, light stabilizers, and curing accelerators. The film-forming aids include one or more of 2,2,4-trimethyl-1,3-pentanediol monoisobutyrate, propylene glycol butyl ether, and diethylene glycol butyl ether. The defoamers include one or more of BYK-057 and BYK-190. The thickeners include nonionic polyurethane thickener RM2020. The substrate wetting agents include one or more of gemini diol polyether, twin siloxane 3, TEGO-270, and octoxyethoxyethanol. The matting agents include one or more of ACEMATT 360 and ED 30. The light stabilizers include the aqueous light stabilizer HALS. The curing accelerators include mercaptopropyl polydimethylsiloxane, 3-mercaptopropionic acid, and diisocyanate.

[0038] Specifically, the film-forming aid includes one or more of 2,2,4-trimethyl-1,3-pentanediol monoisobutyrate, propylene glycol butyl ether, and diethylene glycol butyl ether. 2,2,4-trimethyl-1,3-pentanediol monoisobutyrate has good solubility and volatility. It can lower the minimum film-forming temperature of the coating, enabling the coating to form a uniform film over a wider temperature range. Furthermore, 2,2,4-trimethyl-1,3-pentanediol monoisobutyrate can improve the water resistance and chemical resistance of the coating. Propylene glycol butyl ether can be used as a film-forming aid in coatings to promote film formation and increase the flexibility and impact resistance of the coating. Diethylene glycol butyl ether has good solubility and evaporation rate. It can improve the hardness and gloss of the coating and improve the leveling properties of the coating.

[0039] Specifically, the defoamer includes one or more of BYK-057 and BYK-190. BYK-190 is a silicone-free defoamer, a polyether siloxane copolymer, suitable for water-based coating systems. BYK-057 is a silicone-free defoamer used to prevent foam formation in solvent-free coatings during production, filling, and application. BYK-057 exhibits spontaneous defoaming properties and has no adverse effect on interlayer adhesion.

[0040] Specifically, the thickener includes nonionic polyurethane thickener RM2020. Nonionic polyurethane thickener RM2020 is easily dispersed and does not negatively affect the color or transparency of the coating. It increases the viscosity and rheological properties of the coating, effectively improving its coating performance and uniformity, preventing uneven conductive paths caused by excessively fast or slow flow. Nonionic polyurethane thickener RM2020 exhibits good solvent resistance and stability, unaffected by pH changes, maintaining a stable thickening effect over a wide pH range. This ensures consistent performance of the conductive coating under different conditions. Nonionic polyurethane thickener RM2020 provides stable high shear viscosity, preventing drastic changes in coating consistency during stirring or application, thus helping to ensure coating uniformity.

[0041] Specifically, the substrate wetting agent includes one or more of gemini diol polyether (GEM)5, twinsiloxane 3, TEGO-270, and octoxyethoxyethanol. Gemini diol polyether (GEM)5 has low surface tension, significantly improving wetting effect on the substrate and thus enhancing coating adhesion. Its twin structure makes it more efficient than conventional wetting agents at the same concentration. Furthermore, gemini diol polyether (GEM)5 helps eliminate air bubbles in the coating, improving adhesion. Twinsiloxane 3 combines the low surface tension of silicone with the compatibility of polyether, forming a good wetting layer on the substrate surface, reducing coating defects, and improving coating adhesion and conductivity. It also has a twin structure, making it particularly effective in improving wettability and contributing to improved water resistance and weather resistance of the coating. TEGO-270 is a polyether-modified silicone surfactant suitable for aqueous systems, effectively reducing surface tension and exhibiting good amphiphilicity, improving wetting and leveling properties. TEGO-270 can also be used as an anti-foaming agent to reduce bubble formation in coatings, making it suitable for conductive coatings that require high surface finish. Octyloxyethoxyethanol (AEO-3) has excellent wetting and penetration properties, helping coatings spread better on the substrate and thus improving adhesion.

[0042] Specifically, the matting agent includes one or more of ACEMATT 360 and ED 30. ACEMATT 360 is a highly efficient organic matting agent made of polymer microparticles, exhibiting excellent matting effects. It reduces the surface gloss of the coating by scattering light, giving the coating a soft matte finish. ACEMATT 360 has good dispersibility and compatibility, can be uniformly dispersed in various resin systems, and enhances the weather resistance and abrasion resistance of the coating.

[0043] ED 30 matting agent features high porosity, good dispersibility, smoothness, abrasion resistance, and high transparency. It has virtually no impact on coating performance, remains stable under high shear, does not form hard deposits during storage, and has no adverse effects on curing performance or interlayer adhesion. It provides a high-transparency, haze-free, high-quality surface.

[0044] Specifically, the light stabilizer includes the water-based light stabilizer HALS. The mechanism of action of HALS includes quenching excited-state molecules, capturing free radicals, and repairing damage to polymer chains. It does not absorb ultraviolet light but works by scavenging harmful free radicals generated by ultraviolet irradiation, thereby protecting the polymer from photoaging. HALS provides effective light stability even at extremely low concentrations, requiring only small amounts. Its light stability lasts for a long time and is not easily affected by environmental factors. In coatings, it primarily prevents pigment decomposition, maintaining the color stability of the coating film over a long period. Furthermore, HALS is suitable for water-based systems, has good dispersibility, and can diffuse and disperse in coatings, thus uniformly distributing throughout the coating and improving its light stability.

[0045] Optionally, in some embodiments, TRUELICHT UV 2020 is a high molecular weight HALS with excellent compatibility and anti-extraction properties, and a narrow molecular weight distribution, which ensures consistent performance during processing and use.

[0046] The curing accelerator includes mercaptopropyl polydimethylsiloxane, 3-mercaptopropionic acid, and diisocyanate. Mercaptopropyl polydimethylsiloxane is a polymer with a low glass transition temperature, which can increase the flexibility and reduce the brittleness of the coating, making it more suitable for flexible substrates or surfaces requiring bending. Mercaptopropyl polydimethylsiloxane has a low surface energy, which can help improve the leveling properties of the coating, reduce surface defects, and increase the gloss of the coating. Mercaptopropyl polydimethylsiloxane has a low cohesive energy density, which can reduce the coefficient of friction of the coating and improve its wear resistance.

[0047] Specifically, photoinitiators generate free radicals upon absorbing energy from ultraviolet or visible light. These free radicals can initiate polymerization or cross-linking reactions of mercaptopropyl polydimethylsiloxane, 3-mercaptopropionic acid, and other compounds with unsaturated bonds. The thiol groups in mercaptopropyl polydimethylsiloxane can participate in the formation of the network structure as cross-linking agents. Through the reaction of the thiol groups with the unsaturated bonds of modified polyurethane acrylates or isocyanates, diisocyanates can react with thiol groups to form thiourea bonds or urethane bonds. The reaction between diisocyanates and thiol groups can occur at room temperature, further increasing the reaction rate.

[0048] Optionally, in some embodiments, to avoid the curing accelerator reacting when mixed at room temperature, the curing accelerator can be stirred evenly and then added to the prepared coating before coating or spraying.

[0049] Another object of the present invention is to provide a method for preparing a water-based photocurable conductive coating.

[0050] Furthermore, a method for preparing a water-based photocurable conductive coating includes the following steps:

[0051] (1) The conductive material and the co-solvent are mixed and dispersed and dissolved by ultrasonic waves to obtain the first mixed solution;

[0052] (2) Modified polyurethane acrylate, part of the coupling agent and part of water are mixed and stirred to obtain a second mixed solution;

[0053] (3) Mix the first mixed solution, the second mixed solution, part of the coupling agent, leveling agent, photoinitiator, additives and the remaining water under light-protected conditions to obtain a water-based photocurable conductive coating.

[0054] In step (1), the conductive material is mixed with a co-solvent. Ultrasonic treatment can effectively break up agglomerates, refine the conductive material particles and disperse them evenly, so that the conductive material is fully dispersed and dissolved in the co-solvent to form a homogeneous first mixed solution.

[0055] In step (2), the modified polyurethane acrylate serves as the base resin for the coating, providing adhesion and mechanical properties. A coupling agent is used to improve the interfacial bonding between the filler and the resin, enhancing the coating's adhesion and durability. Under stirring, the modified polyurethane acrylate emulsion and water are mixed uniformly to form a second mixed solution.

[0056] In step (3), the first and second mixed solutions obtained in steps one and two are mixed again, and the remaining coupling agent, leveling agent, photoinitiator, water, and additives are added. The leveling agent helps improve the surface smoothness of the coating and reduces coating defects. The photoinitiator is a key component of UV-curable coatings, capable of initiating polymerization reactions under ultraviolet or visible light irradiation, allowing the coating to cure rapidly. Additives optimize the overall performance of the coating. The entire mixing process requires operation in the dark to prevent premature reaction of the photoinitiator.

[0057] Finally, continue stirring under light-protected conditions to ensure all components are completely and uniformly mixed, forming a water-based photocurable conductive coating. This coating can be applied to various substrates and, after photocuring, forms a conductive coating.

[0058] Optionally, in some embodiments, the ultrasonic dispersion and dissolution time in step 1 is 20-40 min; the stirring speed in step 2 is 1200-1600 rpm and the stirring time is 20-30 min; and the stirring speed in step 3 is 1000-1200 rpm and the stirring time is 30-50 min.

[0059] Another object of the present invention is to provide an application of a method for preparing a water-based photocurable conductive coating.

[0060] Furthermore, the prepared water-based photocurable conductive coating is applied to electronic musical instruments.

[0061] The application of water-based UV-cured conductive coatings in electronic musical instruments provides excellent conductivity and protection. Electronic musical instruments require superior conductivity to ensure the connection and signal transmission between various electronic components. Water-based UV-cured conductive coatings can form a uniform conductive film on the surface of the instrument, ensuring stable connections between electronic components and reliable signal transmission. Conductive coatings can also provide localized electromagnetic shielding, reducing the impact of external electromagnetic interference on the instrument or preventing electromagnetic fields generated by the instrument from interfering with other equipment. Furthermore, water-based UV-cured conductive coatings offer good abrasion resistance and chemical stability, extending the lifespan of the electronic musical instrument.

[0062] Specifically, clean the surface of the electronic instrument, ensuring it is clean, dust-free, and grease-free. Apply or spray a water-based UV-cured conductive coating evenly to the designated areas of the instrument. Irradiate the coated areas with ultraviolet light to cure and form a conductive layer.

[0063] Optionally, in some embodiments, the prepared water-based photocurable conductive coating is applied to an electronic guitar. In the prior art, a layer of copper foil and tin foil is attached to the cover of the electronic guitar's circuit chamber to form a closed loop. Secondly, the various chambers are interconnected, and the shielding of the shifter chamber, pickup chamber, and circuit chamber must be connected together. Using tin foil requires splicing each piece individually to avoid insufficient contact with the circuit chamber. Furthermore, insulating glue cannot be used when splicing and pasting the copper foil and tin foil, and the copper foil and tin foil can easily cut hands. Therefore, the use of water-based photocurable conductive coating can adapt to circuit chambers of different materials and shapes. The photocuring process after spraying is simple to operate, which can not only effectively improve the conductive shielding effect, but also reduce the problem of insufficient contact caused by insufficient adhesion of copper foil and tin foil.

[0064] Compared with the prior art, the present invention has the following advantages:

[0065] 1. The water-based photocurable conductive coating of the present invention uses water to replace part of the solvent, which can reduce the harm to the human body during the production and application process of the coating. The water-based photocurable conductive coating of the present invention can form a uniform conductive film on the surface of the substrate, ensuring the stability of the connection between electronic components and the reliability of signal transmission. The conductive coating can be used to provide local electromagnetic shielding, reducing the impact of external electromagnetic interference on the substrate. The water-based photocurable conductive coating can also provide good mechanical properties and environmental resistance, further extending the service life of the substrate.

[0066] 2. The water-based photocurable conductive coating of the present invention has a low production cost and the photocuring process is energy-efficient, which helps to reduce the overall coating cost. By using water as a solvent to replace traditional organic solvents, the emission of volatile organic compounds can be reduced during the production process, which has a smaller impact on the environment and human health. The preparation process of the water-based photocurable conductive coating is relatively simple, does not require complex equipment and technology, and is easy to produce and apply on a large scale.

[0067] 3. The water-based photocurable conductive coating obtained by the preparation method of this invention can be applied to electronic musical instruments to ensure the smooth flow of current in the circuit, reduce the influence of external electromagnetic fields on the circuit, avoid sound quality distortion, increased noise or decreased volume, and greatly improve the user experience of electronic musical instruments. Detailed Implementation

[0068] To enable those skilled in the art to better understand the technical solutions described in this invention, the following embodiments are provided for illustration. Unless otherwise specified, the raw materials, reagents, or devices used in the following embodiments can be obtained from conventional commercial channels or by existing known methods.

[0069] The present invention will be further described below with reference to specific embodiments:

[0070] Table 1: Weight Component Distribution of the Formulation

[0071]

[0072]

[0073]

[0074] 1. The preparation method of modified polyurethane acrylate is as follows:

[0075] Polyether diol, as the soft segment, is used in a proportion of 50 parts by weight. Diisocyanate, as the hard segment, is used in a ratio of 1:2 with polyether diol. Dimethylolpropionic acid is used in a proportion of 15 parts, and acrylate is used in a proportion of 25 parts. The modified polyurethane acrylate is prepared by adding polyether diol and a certain amount of butyl acetate to a reactor equipped with a stirrer, thermometer, and nitrogen inlet under well-ventilated conditions. Dehydration is carried out for 1-2 hours at a temperature of 105-115℃ and a vacuum degree of -0.080-0.086MPa. Cool to 50-55℃, add diisocyanate, heat to 80-85℃, add catalyst DBTDL, react for 1-2 hours, cool to 30-40℃, add dimethylolpropionic acid, and to prevent further crosslinking reaction, add polymerization inhibitor hydroquinone, react for 0.5-2 hours, cool to room temperature, then add hydroxyethyl methacrylate, and continue stirring under reflux at 60-80℃ for 2 hours. Add neutralizing agent triethylamine to adjust the pH value, and under stirring, slowly add water until a stable emulsion is formed to obtain polyurethane acrylate prepolymer emulsion.

[0076] The synthesized polyurethane acrylate prepolymer emulsion was stirred until homogeneous, and the temperature was controlled at 70-75℃. Bisphenol A epoxy acrylate dissolved in an appropriate amount of ethanol was added, and the reaction was carried out for 1-2 hours. The temperature was then lowered to 50-55℃, and a ring-opening agent, organotin alcohol or triethylamine, was added. The reaction was stirred for 2-3 hours. The temperature was further lowered to 30-40℃, and triethylamine was added to neutralize the reaction for 30-45 minutes. For every 100 parts of polyurethane acrylate prepolymer emulsion, 20-50 parts of deionized water were added under high-speed stirring, and the mixture was sheared and dispersed for 45-60 minutes to obtain a bisphenol A epoxy acrylate modified polyurethane emulsion.

[0077] 2. The preparation method of polyvinyl alcohol modified graphene oxide is as follows: graphene oxide powder is added to dimethyl sulfoxide and subjected to ultrasonic treatment to obtain a uniformly dispersed graphene oxide solution. EDC·HCl (1-ethyl-3-(3-dimethylaminopropyl)carbodiimide hydrochloride) and NHS (N-hydroxysuccinimide) are added to the graphene oxide solution, and polyvinyl alcohol is dissolved in water to form a polyvinyl alcohol (PVA) aqueous solution.

[0078] Activated graphene oxide was slowly added to an aqueous solution of polyvinyl alcohol (PVA) while maintaining the temperature at approximately 60°C and stirring for 4 hours. The product was then separated from the solution by centrifugation or filtration, purified, and dried to obtain polyvinyl alcohol-modified graphene oxide. The polyvinyl alcohol-modified graphene oxide was then added to dimethyl sulfoxide (DMSO) and ultrasonically dispersed to form a dispersion with an effective content of 20-50%. This was then set aside.

[0079] 3. The preparation method of polyvinyl alcohol grafted polyaniline copolymer is as follows: a certain amount of polyvinyl alcohol (PVA) is dissolved in deionized water, heated to boiling, stirred continuously until completely dissolved, and then cooled to room temperature.

[0080] A suitable amount of aniline monomer dissolved in N-methylpyrrolidone was added to a polyvinyl alcohol (PVA) solution, and a small amount of glacial acetic acid was added to adjust the pH to acidic. Then, a suitable amount of ammonium persulfate was added as an oxidant. Under stirring conditions, the reaction was maintained between room temperature and 60°C for 2-4 hours until the reaction was complete. The product was then washed and dried to obtain a polyvinyl alcohol-grafted polyaniline copolymer. The PVA was of medium to high molecular weight. The PVA solution prepared with deionized water was between 5% and 15%. The mass ratio of aniline monomer to PVA was 1:1 to 1:5, the mass ratio of aniline monomer to N-methylpyrrolidone was 1:1.1 to 1:2, glacial acetic acid was used to adjust the pH to 3-5, and the amount of ammonium persulfate was 0.5-2% of the aniline monomer.

[0081] 4. The preparation method of modified multi-walled carbon nanotubes is as follows: An appropriate amount of multi-walled carbon nanotubes are added to glacial acetic acid, and ultrasonic treatment is used to help disperse and form a multi-walled carbon nanotube suspension, avoiding aggregation of the multi-walled carbon nanotubes. A mixture of concentrated nitric acid and concentrated sulfuric acid is prepared at a volume ratio of 1:3.

[0082] The dispersed multi-walled carbon nanotube suspension was slowly added to a pre-prepared mixture. The mixture was reacted at room temperature to 60°C for 4 hours with slow stirring to control the reaction rate and reduce the risk of explosion. After the reaction was complete, the mixture was poured into a large amount of ice water to neutralize excess acid, followed by multiple washes with water until the pH was close to neutral. Finally, it was washed with ethanol to remove residual water and impurities, and the washed carboxylic acid multi-walled carbon nanotubes were collected by vacuum filtration.

[0083] Carboxylic acid multi-walled carbon nanotubes were dispersed in ethanol and ultrasonically dispersed to form a homogeneous dispersion. The dispersion of carboxylic acid multi-walled carbon nanotubes was adjusted to weakly alkaline or neutral with sodium hydroxide.

[0084] γ-aminopropyltriethoxysilane was added to a dispersion of carboxylic acid multi-walled carbon nanotubes. The mass ratio of γ-aminopropyltriethoxysilane to carboxylic acid multi-walled carbon nanotubes was 1:2.

[0085] After adding γ-aminopropyltriethoxysilane, the mixture was stirred at room temperature to 60°C for 2 hours to promote the reaction between γ-aminopropyltriethoxysilane and the carboxyl groups on the surface of carboxylic acid multi-walled carbon nanotubes. The product was washed and dried to obtain γ-aminopropyltriethoxysilane-modified carboxylic acid multi-walled carbon nanotubes.

[0086] Example 1

[0087] The preparation method of the water-based photocurable conductive coating in Example 1 includes the following steps:

[0088] (1) The conductive material and the co-solvent are mixed and dispersed and dissolved by ultrasound for 20 minutes to obtain the first mixed solution;

[0089] (2) After mixing modified polyurethane acrylate, 1 part coupling agent and 5 parts water, stir at a speed of 1200 rpm for 20 min to obtain a second mixed solution.

[0090] (3) The first mixed solution, the second mixed solution, the remaining coupling agent, the leveling agent, the photoinitiator, the film-forming aid, the defoamer, the thickener, the substrate wetting agent, the matting powder, the light stabilizer and the remaining water are mixed and stirred under light-protected conditions. The stirring speed is 1000 rpm and the stirring time is 30 min to obtain the water-based photocurable conductive coating.

[0091] (4) The water-based UV-curable conductive coating is mixed with a curing accelerator and then sprayed onto the surface of the workpiece. The curing light source used is a UV lamp with a wavelength of 360 nm and a light intensity of 756 mJ / cm². 2 .

[0092] Example 2

[0093] The preparation method of the water-based photocurable conductive coating in Example 2 includes the following steps:

[0094] (1) The conductive material and the co-solvent are mixed and dispersed and dissolved by ultrasound for 30 minutes to obtain the first mixed solution;

[0095] (2) Modified polyurethane acrylate, 0.5 parts coupling agent and 5 parts water are mixed and stirred at a speed of 1400 rpm for 30 min to obtain a second mixed solution.

[0096] (3) The first mixed solution, the second mixed solution, the remaining coupling agent, the leveling agent, the photoinitiator, the film-forming aid, the defoamer, the thickener, the substrate wetting agent, the matting powder, the light stabilizer and the remaining water are mixed and stirred under light-protected conditions. The stirring speed is 1100 rpm and the stirring time is 40 min to obtain the water-based photocurable conductive coating.

[0097] (4) The water-based UV-curable conductive coating is mixed with a curing accelerator and then sprayed onto the surface of the workpiece. The curing light source used is a UV lamp with a wavelength of 360 nm and a light intensity of 756 mJ / cm². 2 .

[0098] Example 3

[0099] The preparation method of the water-based photocurable conductive coating in Example 3 includes the following steps:

[0100] (1) The conductive material and the co-solvent are mixed and dispersed and dissolved by ultrasound for 40 minutes to obtain the first mixed solution;

[0101] (2) After mixing modified polyurethane acrylate, 1 part coupling agent and 10 parts water, stir at a speed of 1600 rpm for 30 min to obtain a second mixed solution.

[0102] (3) The first mixed solution, the second mixed solution, the remaining coupling agent, the leveling agent, the photoinitiator, the film-forming aid, the defoamer, the thickener, the substrate wetting agent, the matting powder, the light stabilizer and the remaining water are mixed and stirred under light-protected conditions. The stirring speed is 1200 rpm and the stirring time is 50 min to obtain the water-based photocurable conductive coating.

[0103] (4) The water-based UV-curable conductive coating is mixed with a curing accelerator and then sprayed onto the surface of the workpiece. The curing light source used is a UV lamp with a wavelength of 360 nm and a light intensity of 756 mJ / cm². 2 .

[0104] Example 4

[0105] The preparation method of the water-based photocurable conductive coating in Example 4 includes the following steps:

[0106] (1) The conductive material and the co-solvent are mixed and dispersed and dissolved by ultrasound for 40 minutes to obtain the first mixed solution;

[0107] (2) Modified polyurethane acrylate, 1 part vinyltrimethoxysilane and 10 parts water were mixed and stirred at a speed of 1600 rpm for 30 min to obtain a second mixed solution.

[0108] (3) The first mixed solution, the second mixed solution, the remaining coupling agent, the leveling agent, the photoinitiator, the film-forming aid, the defoamer, the thickener, the substrate wetting agent, the matting powder, the light stabilizer and the remaining water are mixed and stirred under light-protected conditions. The stirring speed is 1200 rpm and the stirring time is 50 min to obtain the water-based photocurable conductive coating.

[0109] (4) The water-based UV-curable conductive coating is mixed with a curing accelerator and then sprayed onto the surface of the workpiece. The curing light source used is a UV lamp with a wavelength of 360 nm and a light intensity of 756 mJ / cm². 2 .

[0110] Comparative Example 1

[0111] The main difference between Comparative Example 1 and Example 4 is that in Comparative Example 1, the modified polyurethane acrylate in Example 4 was replaced with polyurethane, while the other components and operating steps were the same.

[0112] Comparative Example 2

[0113] The main difference between Comparative Example 2 and Example 4 is that the conductive material in Comparative Example 2 is replaced with graphene, while the other components and operating steps are the same.

[0114] Comparative Example 3

[0115] The main difference between Comparative Example 3 and Example 4 is that no curing accelerator is added to the water-based UV-curable conductive coating, which is directly sprayed onto the workpiece surface. The curing light source used is a UV lamp with a wavelength of 360 nm and a light intensity of 756 mJ / cm². 2 The other components and operating procedures are the same.

[0116] Comparative Example 4

[0117] The main difference between Comparative Example 4 and Example 4 is that Comparative Example 4 does not add a cosolvent, while the other components and operating steps are the same.

[0118] The above embodiments and comparative examples were subjected to performance tests. The test methods are shown in Tables 2 and 3. The coating thickness sprayed on the workpiece surface was 3 mm.

[0119] Table 2: Performance Test Results of Examples 1-4

[0120]

[0121]

[0122] Table 3: Performance Test Results of Comparative Examples 1-4

[0123]

[0124] As shown in Tables 2 and 3, in Comparative Example 1, the modified polyurethane acrylate was replaced with polyurethane. In Example 4, the polyurethane acrylate modified with bisphenol A epoxy acrylate exhibits better strength, adhesion, and chemical resistance compared to polyurethane. It also possesses superior physical and mechanical properties and environmental resistance, making it suitable for complex surface treatments or multi-material applications. The network structure formed by the modification with bisphenol A epoxy acrylate helps to disperse the conductive material more uniformly, thereby increasing the load on the conductive material and forming a continuous conductive path, thus improving the conductive shielding effect. Therefore, the surface resistivity of Example 4 is lower than that of Comparative Example 1. Consequently, the conductivity, mechanical strength (pencil hardness, tensile strength, cross-cut test), and environmental resistance (neutral salt spray resistance, aging resistance) of Example 4 are significantly better than those of Comparative Example 1.

[0125] In Comparative Example 2, the conductive material was replaced with graphene. Graphene tends to agglomerate in the coating. Compared to Example 4, graphene in water-based coatings tends to result in insufficient loading and uneven distribution of conductive material. In Example 4, the hydroxyl groups of polyvinyl alcohol can interact with the oxygen-containing functional groups on graphene oxide by forming hydrogen bonds, thereby introducing new reaction sites and enhancing the bonding force between graphene oxide and the coating matrix. This helps to form a denser composite material structure and improves the adhesion, wear resistance, and durability of the coating. Modification with polyvinyl alcohol can effectively improve the conductivity of graphene oxide and can, to some extent, control the density and continuity of the graphene oxide network, giving the coating better conductivity. The addition of PVA improves the processing performance of the material, making conductive coatings based on polyvinyl alcohol (PVA) grafted with polyaniline (PANI) copolymer easier to apply. Conventional coating and spraying methods can be used to form a uniform conductive coating. By grafting hydrophilic polyvinyl alcohol (PVA), the dispersibility and solubility of the copolymer in aqueous and other polar solvents can be improved. This avoids the difficulty of dissolving polyaniline in common solvents due to its rigid backbone and strong intermolecular interactions. The grafted PVA acts as a steric barrier, reducing the aggregation between polyaniline chains, thereby contributing to the formation of a more uniform conductive network and improving the conductivity of the coating. γ-aminopropyltriethoxysilane can effectively improve the surface properties of carbon nanotubes and enhance their compatibility with the coating matrix, which is beneficial to improving the adhesion and stability of the coating. Good dispersibility and interfacial adhesion can reduce the contact resistance between carbon nanotubes. The modified multi-walled carbon nanotubes help to lower the percolation threshold of the conductive coating, that is, good conductivity can be achieved at a lower addition amount. Therefore, the surface resistance of Example 4 is lower than that of Comparative Example 2, and the conductivity is better.

[0126] No curing accelerator was used in Comparative Example 3. The curing accelerator in Example 4 increases the flexibility and reduces the brittleness of the coating, making it more suitable for flexible substrates or surfaces requiring bending. Mercaptopropyl polydimethylsiloxane has a low surface energy, which helps improve the leveling properties of the coating, reduces surface defects, and affects the appearance of the film. The mercapto groups in mercaptopropyl polydimethylsiloxane can act as crosslinking agents in the formation of the network structure. Through the reaction of the mercapto groups with the unsaturated bonds of the modified polyurethane acrylate or isocyanate, diisocyanate can react with the mercapto groups to form thiourea bonds or urethane bonds. The reaction between diisocyanate and mercapto groups can occur at room temperature, further increasing the reaction rate. Therefore, the mechanical strength and environmental resistance of the reactants in Example 4 are better than those in Comparative Example 3.

[0127] In Comparative Example 4, since no co-solvent was added, the conductive material could not be effectively dispersed, and the storage stability of Comparative Example 4 was worse than that of Example 4. At the same time, the conductive material in Comparative Example 4 would be lost, and could not be fully and effectively used in coating application and could not be stably and uniformly coated on the workpiece surface, resulting in higher resistance in Comparative Example 4 and poorer conductivity than that of Example 4.

[0128] Furthermore, by testing the shielding performance using a far-field shielding effectiveness testing device, the shielding effectiveness of the coating obtained in Example 4 after spraying and curing was 24.19-36.28 dB in the 14 kHz-1 GHz frequency band. The shielding effectiveness of the coating obtained in Comparative Example 2 after spraying and curing was 18.31-27.55 dB in the 14 kHz-1 GHz frequency band, and the shielding effectiveness of the coating obtained in Comparative Example 4 after spraying and curing was 21.67-32.82 dB in the 14 kHz-1 GHz frequency band. The water-based photocurable conductive coating of the present invention has a uniformly dispersed conductive material. Compared with the graphene used in Comparative Example 2, Example 4 has a more significant shielding effect on electromagnetic waves and can better isolate external electromagnetic interference. Moreover, the uniform dispersion of the conductive material in Example 4 can increase the amount of conductive material coated after construction, avoiding the inability of precipitated conductive material to disperse into the coating, thus preventing the coating from failing to effectively provide a shielding effect.

[0129] As shown in Tables 2 and 3, the water-based photocurable conductive coating of the present invention uses water to replace part of the solvent, which can reduce the harm to the human body during the production and application process. The water-based photocurable conductive coating of the present invention can form a uniform conductive film on the surface of the substrate, ensuring stable connections between electronic components and reliable signal transmission. Conductive coatings can be used to provide local electromagnetic shielding, reducing the impact of external electromagnetic interference on the substrate. The water-based photocurable conductive coating also provides good wear resistance and chemical stability, extending the service life of the substrate.

[0130] The above description is a preferred embodiment of the present invention. For those skilled in the art, several improvements and modifications can be made without departing from the technical principles of the present invention, and these improvements and modifications should also be considered within the scope of protection of the present invention.

Claims

1. A water-based photocurable conductive coating, characterized in that, The components include the following parts by weight: 30-50 parts modified polyurethane acrylate, 5-15 parts conductive material, 1-3 parts coupling agent, 0.5-1.5 parts leveling agent, 3-6 parts photoinitiator, 20-35 parts water, 10-20 parts cosolvent, and 8-15 parts additives. The conductive material is composed of modified graphene, polyvinyl alcohol graft copolymer, and modified multi-walled carbon nanotubes, and the weight ratio of the three is selected from one of 3:3:2, 3:1:1, 5:5:5, and 4:3:

3. The modified polyurethane acrylate includes bisphenol A epoxy acrylate modified polyurethane acrylate; its preparation method is as follows: polyether diol, diisocyanate, dimethylolpropionic acid and acrylate are added to a closed reactor and reacted to obtain a polyurethane acrylate prepolymer emulsion; bisphenol A epoxy acrylate is dissolved in a solvent and then gradually added to the above prepolymer emulsion, stirred and dispersed to form a stable emulsion; triethylamine is added for ring opening and neutralization, deionized water is added, and shear dispersion is performed to obtain the modified polyurethane acrylate emulsion; The modified graphene is polyvinyl alcohol modified graphene oxide; Polyvinyl alcohol graft copolymer is a polyvinyl alcohol grafted polyaniline copolymer; The modified multi-walled carbon nanotubes are γ-aminopropyltriethoxysilane-modified carboxylic acid multi-walled carbon nanotubes. The additives include film-forming aids, defoamers, thickeners, substrate wetting agents, matting agents, light stabilizers, and curing accelerators. The curing accelerator is composed of mercaptopropyl polydimethylsiloxane, 3-mercaptopropionic acid, and diisocyanate. The cosolvent is polyvinylpyrrolidone. The water-based photocurable conductive coating is used in the circuit compartment of electronic musical instruments and provides electromagnetic shielding. A method for preparing a water-based photocurable conductive coating includes the following steps: (1) Mix the conductive material, co-solvent, and some water, and disperse and dissolve them by ultrasonication for 20-40 minutes to obtain the first mixed solution; (2) Mix the modified polyurethane acrylate, part of the coupling agent and part of the water and stir. The stirring speed is 1200-1600 rpm and the stirring time is 20-30 min to obtain the second mixed solution. (3) Mix the first mixed solution, the second mixed solution, the remaining coupling agent, the leveling agent, the photoinitiator, the film-forming aid, the defoamer, the thickener, the substrate wetting agent, the matting powder, the light stabilizer and the remaining water under light-protected conditions. The stirring speed is 1000-1200 rpm and the stirring time is 30-50 min. The curing accelerator is added after being thoroughly stirred during the preparation of coating or spraying.

2. The water-based photocurable conductive coating according to claim 1, characterized in that: The coupling agent is one or both of vinyltrimethoxysilane and γ-methacryloyloxypropyltrimethoxysilane, and the leveling agent is BYK-333 or GSK-550.

3. The water-based photocurable conductive coating according to claim 1, characterized in that: The photoinitiator is one or more of 2-hydroxy-4-(2-hydroxyethoxy)-2-methylphenylacetone, 2-hydroxy-2-methyl-1-phenyl-1-propanone, 1-hydroxycyclohexylphenyl ketone, and ethyl 2,4,6-trimethylbenzoylphosphonate.

4. The water-based photocurable conductive coating according to claim 1, characterized in that: The film-forming aid includes one or more of 2,2,4-trimethyl-1,3-pentanediol monoisobutyrate, propylene glycol butyl ether, and diethylene glycol butyl ether; the defoamer includes BYK-057; the thickener includes nonionic polyurethane thickener RM2020; the substrate wetting agent includes one or more of gemini diol polyether, twin siloxane 3, TEGO-270, and octoxyethoxyethanol; the matting agent includes ED 30; and the light stabilizer includes the aqueous light stabilizer HALS.

5. The application of the water-based photocurable conductive coating according to claim 1, characterized in that: The prepared water-based photocurable conductive coating is used in the circuit compartment of electronic musical instruments.

Citation Information

Patent Citations

  • Special unsaturated polyester clear primer for musical instrument

    CN104293127A

  • Preparation method for graphene-oxide-based ultraviolet-curable aqueous polyurethane anti-electromagnetic shielding coating

    CN103805049A

  • Antistatic coating composition and preparation method thereof

    CN103819652A

  • Preparation method of carbon fiber / carbon nanotube / organic silicone resin multidimensional hybrid composite material

    CN104151827A

  • Polyurethane acrylate modified ultraviolet light cured water-dilutable resin and preparation method thereof

    CN105754108A